The Importance of Abutment Teeth Preparation Guide for Telescopic Double Crown Restorations with Friction Element - Anindita Apsari; Chaterina Dyah Nanik K (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: Telescopic double crown restoration can be used as an alternative treatment if the patient wants the tooth to be maintained as long as the supporting tooth has a healthy periodontal. In dental preparation telescopic double crown support requires a preparation guide so that the preparation can be acurate. Minimal preparation can cause the results of the telescopic double crown restoration to be overcontoured, so that the patient may occur uncomfortable, speech disorders and esthetic is not good. Objective: to provide information about the importance teeth preparation guidelines for prosthodontic treatment with telescopic double crown restorations. Case: A 72-year-old female patient, coming to the dentist wants to make dentures so that she can chew food well and improve her appearance. The remaining teeth are only 13 and 23. In making the denture, the patient wants the teeth to be retained (not removed) and the denture is aesthetically good. Case Management: Make a diagnostic wax-up on a semiadjustable articulator to estimate the results of restoration, mould the patient's teeth before starting the preparation with three times putty for the preparation guide and making a temporary crown. the first putty mold is cut mesial-distal right in the middle of the incical teeth, the second putty mould is cut in the labial-palatal direction right in the middle of the tooth mould, the third putty mould is fixed on the stock tray to make the temporary crown. Preparation of teeth 13 and 23 with regard to the putty cut preparation guide, then moulding the maxilla and mandibula with double impressions using an individual tray, after that make the temporary crown directly with the third putty mould. Conclusion: The preparation guide of teeth is very necessary so that the making of telescopic double crown restorations is not overcontoured, so that esthetic and retention can be achieved which are good and do not cause speech disorders.